ANALISIS BOPO, NON PERFORMING LOAN (NPL) DAN LOAN TO DEPOSIT RATIO (LDR) UNTUK MENINGKATKAN PROFITABILITAS (Studi Kasus Pada Pt. Bank Maluku-Malut Di Kota Ambon) - David Daniel Khurnala (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
In this study, there were three hypotheses tested, namely (1) It is assumed that OEOI has a positive effect on the profitability of PT. Bank Maluku-Malut Ambon City, (2) It is assumed that NPL has a negative effect on the profitability of PT. Bank Maluku-Malut Ambon City, (3) It is assumed that the liquidity ratio has a positive effect on the profitability of PT. Bank Maluku-Malut Ambon City.The population in this study were all financial reports at PT. Bank Maluku-Malut which had been published from 2015-2019, with samples of financial report data in the form of balance sheets and income statements at PT. Bank Maluku-Malut from 2015-2019 as many as 60 samples. The analysis technique used was multiple linear regression analysis. The t-test was used to test the hypothesis. The results of this study were (1) OEOI had a positive effect on profitability, (2) NPL had a positive effect on profitability, and (3) LDR had a negative effect on profitability.Keywords: Operating Expenses to Operating Income (OEOI), Non Performing Loan (NPL), and Loan To Deposit Ratio (LDR), profitability ratio, ROA